Comparative study of abrasion via microindentation and microscratch tests of reinforced and unreinforced lamellar cast iron - Mohammed Mendas; Stéphane Benayoun (Friction)
Abstract This study compares micro-abrasive wear in two kinds of grey cast iron. Classical lamellar cast iron with fully pearlitic matrix (FGL1) and lamellar micro-alloyed cast iron with phosphorus and boron (FGL2) are used. FGL2 has a fully pearlitic matrix reinforced by the hard phosphorus eutectic phase. The microstructures of these two types of iron are mechanically characterized using nanoindentation tests. Vickers microindentation and microscratch tests are also performed on these iron samples. The indent and scratch images obtained via scanning electron microscopy were used to compare the scratch damage to the two kinds of iron. The friction coefficient is discussed in terms of applied load, indenter attack angle, and scratch damage. Nanoindentation tests show an improvement in graphite’s mechanical properties and an increase in the matrix hardness of the FGL2, relatively to FGL1. The same damage forms for both microindentation and microscratch testing were observed for the two iron samples. However, cracking of the hard phase is observed in FGL2. The results show that the scratching of the micro-alloyed iron (FGL2) leads to less matrix damage and to an extended microploughing wear mechanism. However, at low normal load, the reinforcement of the matrix can increase the friction coefficient.